ANGER AND HOSTILITY IN CORONARY ARTERY DISEASE - Fernández-Abascal, Enrique G.; Martín Díaz, Mª. Dolores (Anales de Psicología / Annals of Psychology)
This study examines the role of emotions of anger and hostility as factors that contribute to the increased risk of suffering from coronary artery diseases. Four groups of population are compared: patients with coronary artery diseases (N=35), cadets selected to receive a formation of jet plane pilots (N=53), high school teachers (N=34), and employees of a medical emergency service and of a construction company (N=35). With each group a measure was applied to evaluate the angerhostility components. When the groups were compared, the results showed significant differences in all the scales between the group of patients with coronary artery diseases and group of cadets, the group of patients with coronary artery diseases reached the highest pointing in all scales; the groups of teachers and emergency/construction company were situated in the middle of the scale. About the reactions that these factors establish in each group, is very important the positive relation between all the components of the anger factor (four scales) and total hostility in all the groups, except the group of patients with coronary artery diseases where the relation is only established between the component of Anger/In and Hostility. The results obtained in this study don't show a direction in the anger factor, the data indicate quantity, the patients with coronary artery diseases get higher scores in all the components of the anger factors and total hostility than the patients without coronary artery diseases.